Mathematical Modeling on Human Papillomavirus (HPV): Transmission Dynamics and Impact on Cervical Cancer - Sayooj Aby Jose; Stephen Patrick Nelson; Ramachandran Raja; Gayathry Radhakrishnan Menon; Anuwat Jirawattanapanit (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
One of the most common diseases affecting women globally is cervical cancer, which contributes significantly to the global cancer burden. Its beginning is largely caused by the human papillomavirus (HPV), especially in young females, and a growing percentage of cases develop from benign tumors. The dynamics of HPV transmission and its influence on the development of cervical cancer are described in this study using a deterministic mathematical model. The fundamental characteristics of the model, such as positivity and boundedness, are carefully examined. Furthermore, the equilibrium points for endemic and disease-free conditions are determined, and their stability on a local and global scale is examined in relation to the basic reproduction number, R0. Furthermore, a detailed sensitivity analysis is conducted to identify the key parameters that most significantly influence the transmission dynamics and progression of the disease. Numerical simulations are performed to illustrate the impact of parameter variations and to validate the analytical findings. The results provide valuable insights for effective public health intervention and control strategies for HPV-related cervical cancer.